Controlled synthesis of a porous single-atomic Fe–N–C catalyst with Fe nanoclusters as synergistic catalytic sites for efficient oxygen reduction. Issue 16 (29th June 2022) - Fan, Lili; Zhang, Ling; Li, Xuting; Mei, Hao; Li, Mengfei; Liu, Zhanning; Kang, Zixi; Tuo, Yongxiao; Wang, Rongming; Sun, Daofeng
Abstract : A porous single-atomic Fe–N–C catalyst is prepared with the presence of Fe nanoclusters to increase the adsorption energy of OOH* on the single Fe atom and lower the energy barrier for OOH formation, thus improving the ORR activity. Abstract : Single-atomic Fe–N x sites have been widely accepted as active sites for the oxygen reduction reaction (ORR), while the roles played by other symbiotic Fe moieties (such as Fe clusters) are still contentious. Synthesis of Fe–N–C catalysts possessing both Fe–N x sites and Fe clusters and investigation of their catalytic mechanism are essential but challenging. Herein, the controlled synthesis of a model catalyst is successfully achieved using Fe(II)–phenanthroline (Phen) complexes as the only precursor. Through a solid-phase preparation process, Fe–Phen complexes are synthesized on the surface of silica that is used as a hard template for introducing porosity into the carbon structure. The high density of Fe centers facilitates the simultaneous generation of single atomic Fe–N x sites and Fe clusters, severe aggregation of which is impeded by the silica template. The as-prepared catalyst delivers an efficient ORR performance in an alkaline environment. Combining with computational analysis, the synergistic catalytic mechanism between the Fe–N x sites and Fe clusters is revealed that the neighboring Fe clusters can increase the adsorption energy of OOH* on the Fe atom of Fe–N x sites and lower the energy barrier for the formation of the OOH intermediate, thus accelerating the catalytic process. This study provides insights into the future design and synthesis of efficient Fe–N–C catalysts.